Sobre GAFF, Alan D. y Donald H. GAFF (editores), From the Halls of the Montezumas, Mexican War Dispatches from James L. Freaner, Writing under the Pen Name "Mustang", Denton, University of North Texas Press, 2019, (War and the Southwest Series, 14), 477 p (Tzintzun. Revista de Estudios Históricos, 2021)
-